Concurrent density distribution and build orientation optimization of additively manufactured functionally graded lattice structures. (October 2020) - Nguyen, Cong Hong Phong; Choi, Young
Abstract: Functionally graded conformal lattice structures (FGCLSs) are a particular type of lattice structure in which lattice unit cells are populated following structural boundaries and the density of the lattice unit cells is optimally distributed. Additionally, additively manufactured parts are reported to have anisotropic mechanical properties that highly depend on the part build orientations. This is extremely important in designing FGCLS parts where orientations of lattice unit cells are not uniform, making the build orientation selection more challenging. In this study, a concurrent density distribution and build orientation optimization framework of additively manufactured FGCLSs for structure-performance maximization was developed. The proposed approach was validated via case studies on lightweight part design for compliance minimization, with three design examples having geometric complexity levels varying from low to high. The results showed that the proposed concurrent optimization method was more effective at enhancing structural performance than optimizing only the density distribution of the structure. In addition, the build orientation configurations determined by the proposed method provided better structural performance compared to those determined using other slicing software. Moreover, compared to the pseudo-worst build orientation configuration, the configuration obtained from the proposed approach could enhance structural performance by up to 47.56%. Highlights: A concurrent structure–process optimum part design with conformal lattice structure. Euler's angle was applied for build orientation modeling. Build orientation dependent anisotropic lattice scaling law was developed. Density distribution (structure) and build orientation (process) are concurrently optimized.